Three-year visual and anatomic results of administrating intravitreal bevacizumab in inflammatory ocular neovascularization - Mansour, Ahmad M.; Mackensen, Friederike (Canadian journal of ophthalmology, 2012)
Objective: To assess the 3-year visual outcome of intravitreal bevacizumab in inflammatory ocular neovascularization. Design: Experimental study. Methods: Retrospective multicenter consecutive case series in 81 patients with inflammatory ocular neovascularization refractory to standard therapy and treated with intravitreal bevacizumab. The outcome measures included improvement of best corrected visual acuity expressed as logarithm of minimum angle of resolution (logMAR) and paired comparison decrease in central foveal thickness by optical coherence tomography. Results: Mean best corrected visual acuity improved from baseline 0.699 (6/30 or 20/101) (SD 0.434) to 0.426 (6/16 or 20/53) (SD 0.428) (n = 81; p < 0.001), a gain of 2.7 lines (median 3 injections; 81 eyes; 81 patients). Paired comparisons revealed significant central foveal flattening at 3 years of 97.9 μm (n = 51; p < 0.001). In a subgroup analysis, visual improvement was significant for ocular histoplasmosis (p = 0.026); multifocal choroiditis (p = 0.05); serpiginous choroiditis (p = 0.028); ocular toxoplasmosis (p = 0.042); and punctate inner choroidopathy (p = 0.015). In a subgroup analysis, foveal flattening was significant for ocular histoplasmosis (p = 0.004); multifocal choroiditis (p = 0.007); serpiginous choroiditis (p = 0.011); and punctate inner choroidopathy (p = 0.001). Of the group, 5 eyes developed submacular fibrosis, 1 eye retinal pigment epithelial tear, and 1 eye macular ischemia in the context of vasculitis. Conclusion: At 3 years, intravitreal bevacizumab sustained significant visual improvement of 2.7 lines and significant foveal flattening of 98 μm in a wide variety of inflammatory ocular diseases without major complications after a median of 3 injections. Objet: Évaluation du résultat visuel de 3 années de traitement intravitréen au bévacizumab pour une néovascularisation oculaire inflammatoire. Méthodes: Série rétrospective de cas consécutifs dans plusieurs centres chez 81 patients atteints de néovascularisation oculaire inflammatoire, réfractaires à la thérapie standard et traités au bévacizumab intravitréen. La mesure des résultats comprenait l'amélioration de la meilleure acuité visuelle corrigée, exprimée sous forme de logarithme de l'angle minimum de résolution (logAMR) et par comparaison appariée de la réduction de l'épaisseur de la fovéa centrale selon la tomographie par cohérence optique. Résultats: La moyenne de la meilleure acuité visuelle corrigée s'est améliorée, allant de la base de 0,699 (6/30 ou 20/101) (ÉT 0,434) à 0,426 (6/16 ou 20/53) (ET 0,428) (n = 81; p < 0,001), soit un gain de 2,7 lignes (moyenne de 3 injections; 81 yeux; 81 patients). Les comparaisons appariées ont révélé après 3 ans un important aplanissement central de 97,9 microns (n = 51; p < 0,001). Dans une analyse de sous-groupe, l'amélioration visuelle a été significative pour l'histoplasmose oculaire (p = 0,026); la choroïdite multifocale (p = 0,05); la choroïdite serpigineuse (p = 0,028); la toxoplasmose oculaire (p = 0,042); et la choroïdite ponctuée interne (p = 0,015). Dans l'analyse d'un sous-groupe, l'aplanissement de la fovéa était significative pour l'histoplasmose oculaire (p = 0,004); la choroïdite multifocale (p = 0,007); la choroïdite serpigineuse (p = 0.011); et la choroïdite ponctuée interne (p = 0,001). Cinq yeux ont développé une fibrose sous-maculaire; un œil, une déchirure de l'épithélium pigmentaire de la rétine; et un œil, une ischémie maculaire dans le contexte d'une vasculite. Conclusion: Après 3 ans, le bévacizumab intravitréen avait soutenu une amélioration visuelle significative de 2,7 lignes et un important aplanissement de 98 microns de la fovéa dans une grande variété de maladies oculaires inflammatoires sans complications majeures, après une médiane de 3 injections.